Soft Malleable Vesicles: versatile carriers for efficient topical delivery of fungal therapeutics - Gupta, Preeti; Jha, Antesh Kumar; Prasad, Mahesh; Kushwaha, Poonam (Drug Research, 2020)
Fungal infections have become a subject of great concern and the incidence of fungal infections is increasing, presenting an enormous challenge to healthcare professionals. Since most of the fungal infections are occurring over the skin, the treatment option of these infections always involves topical application. However, in topical delivery drug reaches into systemic circulation through different barriers of skin. Nevertheless, due to the low permeability, skin restricts the movement of many drugs. Hence, a delivery system is required, which deliver the medicament into the skin layers or through the skin and into the systemic circulation. Ethosomes or Soft malleable vesicles are the novel lipid vesicular carrier that offer improved skin permeability and efficient delivery due to their structure and composition. They contain high concentration of ethanol, which increases the fluidity of the skin. Therefore, in the present paper, we have explored the utility of ethosomal systems in the topical treatment of fungal infections. Structure, compositions types, mechanism and techniques of preparation of ethosome also discussed in the paper.
Keywords: Ethosome; fungal infection; topical drug delivery; penetration mechanism; methods of preparation; application in fungal therapeutics.